Pengaruh Profitabilitas, Likuiditas Dan Leverage Terhadap Harga Saham Pada Perusahaan Farmasi - Arya Shena, Niko; Utomo, Dwiarso (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
This research aims to analyze share price movements on the Indonesia Stock Exchange from 2018 to 2022 in relation to profitability, liquidity and leverage. Return on Equity (ROE) is used to assess profitability, while Current Ratio (CR) is used to assess liquidity and Debt to Equity Ratio (DER) is used to assess leverage in this research. Eleven pharmaceutical companies were randomly selected for data collection for this study. Based on the sample criteria used, seven drug manufacturers have met the requirements for 2018–2022. Linear tests, classical assumption tests, model tests, and hypothesis tests are just some of the statistical procedures used in this test. The results of this research show that profitability has quite a large influence on share prices, but liquidity and leverage were found to have no influence on share prices.